The ice bear - Morris, Jackie (London : Frances Lincoln Children's Books, 2010)
A hunter and his wife find a child in the Arctic and begin to raise him as their own, but on the day the child wanders off, a bear comes to take him back to his real mother and the hunter vows to kill the creature that took his child.
"Janetta Otter-Barry Books"--P. facing t.p.
3.1
K-3
K-3
Keywords: Arctic peoples -- Juvenile fiction; Bears -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Arctic peoples -- Fiction; Bears -- Fiction; Human-animal relationships -- Fiction; Arctic peoples -- Fiction; Bears -- Fiction; Human-animal relationship -- Fiction; Arctic regions -- Juvenile fiction; Arctic regions -- Fiction; Arctic regions -- Fiction; Picture books for children